Comparative Analysis of the Mechanical Performance of Timber Flat Truss Typologies for Different Strength Classes via Optimization Algorithm - Moraes, Matheus Henrique Morato de (2023)
This study aimed to compare the mechanical performance of two truss typologies, the modified Fan and Howe trusses, using five different wood species: Cambará-rosa, Cupiúba, Angelimpedra, Garapa, and Jatobá. The spans considered were 6, 9, 12, and 15 m, and the optimization algorithm used was a swarm intelligence algorithm to minimize the structure weight. The study found that wood is a sustainable and viable option for truss constructions, with different wood species having distinct mechanical properties that must be considered when designing the structure. The Howe truss typology presented lower results for the objective function in comparison with the modified Fan truss. The distribution of normal forces in the truss correlated with the characteristic strength in compression and tensile of the species. The Howe truss typology presented a larger amplitude in relation to the modified Fan truss typology in most of the conditions adopted for the Ultimate Limit State constraints. Constraints associated with deflection in the immediate condition were observed to limit the optimization process. The study used the matrix analysis method to evaluate internal efforts and nodal displacements in the trusses. In summary, this study demonstrates the importance of considering all constraints when dimensioning timber structures and the benefits of using different wood species for sustainable construction.